Usman Janatin and Harun Thohir: A Deep Heroic Story of Indonesia-Malaysia Confrontation (1963-1968) for High School History Materials - Asnewastri Asnewastri; Ahmad Fakhri Hutauruk; Andres M. Ginting; Jalatua Habungaran Hasugian; Ahmad Arif Budiman (STAI Hubbulwathan Duri, 2023)
This article discusses the crucial role of Usman Janatin and Harun Thohir in the confrontation between Indonesia and Malaysia in the 1963–1968 period, presenting an in-depth perspective for understanding history at the Class XII high school level. As the two central figures in this conflict, Usman Janatin and Harun Thohir are in the spotlight, presenting stories of heroism and service that shape the history of relations between the two countries. Data was collected through literature study, document analysis, and interviews. Through content analysis which consists of four steps, namely data procurement, unit determination, recording/coding, inference, and data analysis. This article provides a comprehensive picture of the Indonesia-Malaysia confrontation and the cultural, political and military roles played by Usman Janatin and Harun Thohir. It is hoped that this article will be a valuable resource for Class XII high school students who are studying regional history, providing deeper insight into the period of confrontation and its impact on the two countries. By exploring this heroic story, it is hoped that it can motivate students to better appreciate the spirit of patriotism and devotion to their homeland, as well as increase their understanding of the dynamics of relations between countries in the context of modern history.